Green synthesis of Zinc Oxide nanoparticles for enhanced adsorption of lead ions from aqueous solutions: equilibrium, kinetic and thermodynamic studies - Azizi, Susan; Shahri, Mahnaz Mahdavi; Mohamad, Rosfarizan (MDPI, 2017)
In the present study, ZnO nanoparticles (NPs) were synthesized in zerumbone solution by a green approach and appraised for their ability to absorb Pb(II) ions from aqueous solution. The formation of as-synthesized NPs was established by X-ray diffraction (XRD), Transmission Electron Microscopy (TEM), and UV–visible studies. The XRD and TEM analyses revealed high purity and wurtzite hexagonal structure of ZnO NPs with a mean size of 10.01 ± 2.6 nm. Batch experiments were performed to investigate the impact of process parameters viz. Pb(II) concentration, pH of solution, adsorbent mass, solution temperature, and contact time variations on the removal efficiency of Pb(II). The adsorption isotherm data provided that the adsorption process was mainly monolayer on ZnO NPs. The adsorption process follows pseudo-second-order reaction kinetic. The maximum removal efficiencies were 93% at pH 5. Thermodynamic parameters such as enthalpy change (ΔH0), free energy change (ΔG0), and entropy change (ΔS0) were calculated; the adsorption process was spontaneous and endothermic. The good efficiency of the as-synthesized NPs makes them attractive for applications in water treatment, for removal of heavy metals from aqueous system.